2005
DOI: 10.1017/s0031182005008073
|View full text |Cite
|
Sign up to set email alerts
|

Germ-free mice produce high levels of interferon-gamma in response to infection with Leishmania major but fail to heal lesions

Abstract: In order to investigate the importance of the host microbiota on differentiation of T cell subsets in response to infection, Swiss/NIH germ-free mice and conventional (microbiota-bearing) mice were infected with Leishmania major, and lesion development, parasite loads, and cytokine production were assessed. Germ-free mice failed to heal lesions and presented a higher number of parasites at the site of infection than their conventional counterparts. In addition, histopathological analysis indicated a higher den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…Our results showed that germfree mice died much earlier after bacterial infection, whereas conventional animals, which are capable of inflaming in response to the bacterial challenge, survived for .3 d. Our results are in agreement with others, which demonstrated the increase of susceptibility to parasite infection in absence of commensal microbiota. For example, germ-free mice have decreased capacity to deal with Leishmania major (24) and Trypanosoma cruzi infections (25). Altogether, these experiments in germfree mice would suggest that the ability to inflame in response to bacteria, and possibly other parasites, is evolutionarily relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that germfree mice died much earlier after bacterial infection, whereas conventional animals, which are capable of inflaming in response to the bacterial challenge, survived for .3 d. Our results are in agreement with others, which demonstrated the increase of susceptibility to parasite infection in absence of commensal microbiota. For example, germ-free mice have decreased capacity to deal with Leishmania major (24) and Trypanosoma cruzi infections (25). Altogether, these experiments in germfree mice would suggest that the ability to inflame in response to bacteria, and possibly other parasites, is evolutionarily relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures of spleen cells and lymph nodes were performed as previously described (Oliveira et al 2005). Cells were cultured in medium alone or with 50 µg/mL of a homolog antigen for 24 h for TNF assays or for 72 h for IFN-γ and IL-10 assays.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in medium alone or with 50 µg/mL of a homolog antigen for 24 h for TNF assays or for 72 h for IFN-γ and IL-10 assays. IFN-γ was assayed using the monoclonal antibody R46A2, a polyclonal rabbit anti-mouse IFN-γ prepared in our laboratory and an anti-rabbit IgG conjugated with peroxidase (Zymed Laboratories, Inc, San Francisco, CA, USA) (Oliveira et al 2005). ABTS (Sigma-Aldrich, Inc, St. Louis, MO, USA) and hydrogen peroxide were used as substrates for peroxidase.…”
Section: Methodsmentioning
confidence: 99%
“…First, colonization by commensal microorganisms is key to immune development. [9][10][11][12] Second, the commensal community keeps in check invading pathogens and prevents them from expressing virulence. 13,14 Third, the intestinal microbiota appears to digest glycans and regulate fat storage in mice and potentially in humans.…”
Section: Gut Microbiota Health and Diseasesmentioning
confidence: 99%